2020
DOI: 10.1038/s41467-020-15564-7
|View full text |Cite
|
Sign up to set email alerts
|

TAGAP instructs Th17 differentiation by bridging Dectin activation to EPHB2 signaling in innate antifungal response

Abstract: The TAGAP gene locus has been linked to several infectious diseases or autoimmune diseases, including candidemia and multiple sclerosis. While previous studies have described a role of TAGAP in T cells, much less is known about its function in other cell types. Here we report that TAGAP is required for Dectin-induced anti-fungal signaling and proinflammatory cytokine production in myeloid cells. Following stimulation with Dectin ligands, TAGAP is phosphorylated by EPHB2 at tyrosine 310, which bridges proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…2c). rs654690, associated with psoriasis, IBD, and RA, falls page 10 of 58 preferentially in the accessible chromatin of Tregs and contacts the TAGAP promoter ~50kb downstream 23 ; TAGAP is a gene that has been shown to play a role in Th17 cell differentiation and thymocyte trafficking [24][25][26] (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…2c). rs654690, associated with psoriasis, IBD, and RA, falls page 10 of 58 preferentially in the accessible chromatin of Tregs and contacts the TAGAP promoter ~50kb downstream 23 ; TAGAP is a gene that has been shown to play a role in Th17 cell differentiation and thymocyte trafficking [24][25][26] (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…IDO inhibitors can be used as immunometabolic adjuvants which safely and potently facilitate the e cacy of immunotherapy [22]. T-cell activation Rho GTPase-activating protein (TAGAP) is a GAP-domain containing protein, and was found to exert a role in T-cell differentiation [23]. ZHAO et al reported that the expression level of TAGAP was related to the positive number of lymph nodes in the prostate cancer [23].…”
Section: Discussionmentioning
confidence: 99%
“…T-cell activation Rho GTPase-activating protein (TAGAP) is a GAP-domain containing protein, and was found to exert a role in T-cell differentiation [23]. ZHAO et al reported that the expression level of TAGAP was related to the positive number of lymph nodes in the prostate cancer [23]. Perforin 1 (PRF1) encodes a protein with structural similarities to complement component C9 that is important in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell activation Rho GTPaseactivating protein (TAGAP) is a GAP-domain containing protein and was found to exert a role in T-cell differentiation [27]. ZHAO et al reported that the expression level of TAGAP was related to the positive number of lymph nodes in prostate cancer [27]. Perforin 1 (PRF1) encodes a protein with structural similarities to complement component C9 that is important in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…IDO inhibitors can be used as immune-metabolic adjuvants which safely and potently facilitate the e cacy of immunotherapy [26]. T-cell activation Rho GTPaseactivating protein (TAGAP) is a GAP-domain containing protein and was found to exert a role in T-cell differentiation [27]. ZHAO et al reported that the expression level of TAGAP was related to the positive number of lymph nodes in prostate cancer [27].…”
Section: Discussionmentioning
confidence: 99%